A portable 2D force binding system for cross-country skiing - a validation study - Lindinger, S. J.; Ohtonen, O.; Lemmettylä, T.; Seppälä, S.; Linnamo, V. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The aim of the present study was to design and validate a 2D force binding system for classic and skating technique fulfilling the requirements of modern cross-country skiing research in the field and lab.